KESESUAIAN SARANA PRASARAN UTILITAS DAN BANGUNAN PASAR SESUAI SNI 8152-2015 TENTANG PASAR RAKYAT (PADA PASAR TAMBUN SELATAN) - Noval Abdurohim Hafish; Anisah Anisah; Prihantono Prihantono (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2021)
This study aims to determine the suitability of the Tambun Selatan People's Market based on the existing standards in SNI 8152-2015 concerning the People's Market, and to find out people's perceptions and to evaluate the availability of facilities and infrastructure and public utilities in accordance with SNI 8152-2015. The research method used in this research is literature study and survey. The results showed that observations with SNI 8152-2015 stated that the buildings and infrastructure of the Tambun People's Market were not in accordance with SNI 8152-2015 concerning the People's Market, while those that were not in accordance with SNI 8152-2015 were lighting and circulation, corridors, parking areas, areas. loading and unloading, security posts, health posts, drainage and waste management, and in accordance with SNI 8152-2015 are construction, arrangement of trading rooms, prayer rooms, clean water networks, bathrooms and toilets, and fire prevention. Efforts that need to be made by market managers are to repair damaged facilities that are not in accordance with standards and to procure facilities that are not yet available in the market according to standards.